2010
DOI: 10.1111/j.1096-3642.2010.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Three new species of Callulina (Amphibia: Anura: Brevicipitidae) highlight local endemism and conservation plight of Africa's Eastern Arc forests

Abstract: Material ascribed to the genus Callulina from north-east Tanzania and south-east Kenya is assessed. Three new species of Callulina are described from the North (Callulina laphami sp. nov.) and South (Callulina shengena sp. nov. and Callulina stanleyi sp. nov.) Pare Mountains in Tanzania. The species are diagnosed based on morphological, acoustic, and molecular data. A new key to the species of Callulina is provided. Based on an interpretation of the International Union for Conservation of Nature (IUCN) red lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Recent surveys conducted on isolated rain forests of some Tanzanian mountains have revealed an extraordinary diversity of frogs, with many species restricted to few or even one mountain block (e.g. De Sá et al ., ; Loader et al ., ). These findings are consistent with studies suggesting that isolation and reduced dispersal can result in greater differentiation and higher endemism with increasing elevation (Brown, ).…”
Section: Introductionsupporting
confidence: 92%
“…Recent surveys conducted on isolated rain forests of some Tanzanian mountains have revealed an extraordinary diversity of frogs, with many species restricted to few or even one mountain block (e.g. De Sá et al ., ; Loader et al ., ). These findings are consistent with studies suggesting that isolation and reduced dispersal can result in greater differentiation and higher endemism with increasing elevation (Brown, ).…”
Section: Introductionsupporting
confidence: 92%
“…This shows distinctiveness of highland amphibian fauna from those at the lowland. Recent taxonomic studies elsewhere in the Eastern Arc Mountains have shown distinctiveness in some of the isolated populations, such as Callulina (Loader et al, 2010). In the Uluguru South Mountains, at least three species of Nectophrynoides are known, one of which, N. viviparus, was found at more than one altitudinal zone ( Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…Specimens of East African brevicipitids were obtained by fieldwork in Tanzania and Ethiopia between 2000 and 2012 (see Appendix S1 in Supporting Information). For EABR brevicipitids, we sampled multiple populations of all known species of the family Brevicipitidae except for Probreviceps rhodesianus, and a Callulina population from the Shimba Hills that might be a new species (Loader et al, 2010a). We surveyed all EAM for brevicipitids and included samples of all known populations ( Fig.…”
Section: Taxon Samplingmentioning
confidence: 99%
“…Alignments of partial 12S, 16S, cytochrome b (cytb), recombination-activating gene 1 (rag1) and chemokine (CXC motif) receptor 4 (cxcr4) sequences were assembled based on previously published (Loader et al, , 2010aMenegon et al, 2011) and newly generated data. We sampled all specimens for three mitochondrial gene sequences and sampled seven representatives of the main EABR lineages for rag1 and cxcr4 (Appendix S1).…”
Section: Phylogeneticsmentioning
confidence: 99%